WOMEN’S LANGUAGE FEATURES FOUND IN FEMALE CHARACTER’S UTTERANCES IN THE DEVIL WEARS PRADA MOVIE - Oktapiani, TIka; Natsir, M; Setyowati, Ririn (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2017)
ABSTRACT The research entitled women’s language features found in female character’s utterances in The Devil Wears Prada Movie, aims to identify the women’s language features based on Lakoff’s theory and also to identify language functions served by women’s language features found in The Devil Wears Prada movie based on Jakobsen’s theory. This research was conducted by using descriptive qualitative method, while for collecting the data were watching the movie several times, reading script movie and underlining female character’s utterances containing the women’s language features. From ten features of women’s language, the researcher found nine features used by the female character in The Devil Wears Prada Movie. They are lexical hedges or fillers (7), tag question (3), rising intonation on declarative (2), empty adjectives (3), precious color term (1), intensifiers (10), super polite form (4), hypercorrect grammar (0), avoidance of strong swear words (3) and emphatic stress (3). Intensifiers are the most frequent women’s language features used by female characters in The Devil Wears Prada movie because they want to emphasize or strengthen their utterances deeply to attract addressee’s attention using intensifiers. Meanwhile, hypercorrect grammar did not occur in this research because the female characters mostly used informal language in their dialogue to shorten the gap among the characters. Then, there are language functions served by women’s language found in female character’s utterances in The Devil Wears Prada movie. They are expressive function, directive function and metalinguistic function. Key words: women’s language, women’s language features, The Devil Wears Prada  ABSTRAK  Penelitian ini bertujuan untuk mengidentifikasi fitur-fitur bahasa wanita berdasarkan teori Lakoff dan juga untuk mengidentifikasi fungsi bahasa yang disajikan oleh fitur bahasa wanita yang terdapat dalam film The Devil Wears Prada berdasarkan teori Jakobsen. Penelitian ini dilakukan dengan menggunakan metode deskriptif kualitatif, sedangkan untuk mengumpulkan data adalah menonton film, membaca naskah film dan menggari bawahi ucapan karakter perempuan yang mengandung fitur-fitur bahasa wanita. Dari sepuluh fitur bahasa wanita, peneliti menemukan sembilan fitur yang digunakan oleh karakter wanita dalam The Devil Wears Prada Movie, lexical hedges atau filler7), tag question (3), rising intonation on declarative (2), empty adjectives (3), precise color term (1), intensifiers (10), super polite form (4), hypercorrect grammar (0), avoidance of strong swear word (3) dan emphatic stress (3). Intensifiers adalah fitur bahasa wanita yang paling sering digunakan oleh karakter wanita dalam film The Devil Wears Prada karena mereka ingin menekankan atau memperkuat ucapan mereka secara mendalam untuk menarik perhatian penerima dengan menggunakan intensifiers. Sementara itu, tata bahasa hypercorrect tidak terjadi dalam penelitian ini karena karakter wanita kebanyakan menggunakan bahasa informal dalam dialog mereka untuk memperpendek jarak antar karakter. Kemudian, ada fungsi bahasa yang disajikan oleh bahasa wanita yang ditemukan dalam ujaran karakter wanita dalam film The Devil Wears Prada. Mereka adalah fungsi ekspresif, fungsi direktif dan fungsi metalinguistik. Kata kunci: bahasa wanita, fitur-fitur bahasa wanita, The Devil Wears Prada